Exercise training for people following curative intent treatment for non-small cell lung cancer: a randomized controlled trial - Cavalheri, Vinicius; Jenkins, S.; Cecins, N.; Gain, K.; Phillips, M.; Sanders, L.; Hill, K. (ASSOCIACAO BRASILEIRA PESQUISA POS-GRADUACAO FISIOTERAPIA-ABRAPG-FT, 2017)
Objective: In people following curative intent treatment for non-small cell lung cancer, to investigate the effects of supervised exercise training on exercise capacity, physical activity and sedentary behavior, peripheral muscle force, health-related quality of life, fatigue, feelings of anxiety and depression, and lung function. Method: This pilot randomized controlled trial included participants 6–10 weeks after lobectomy for non-small cell lung cancer or, for those who required adjuvant chemotherapy, 4–8 weeks after their last cycle. Participants were randomized to either 8 weeks of supervised exercise training (exercise group) or 8 weeks of usual care (control group). Prior to and following the intervention period, both groups completed measurements of exercise capacity, physical activity and sedentary behavior, quadriceps and handgrip force, HRQoL, fatigue, feelings of anxiety and depression, and lung function. Intention-to-treat analysis was undertaken. Results: Seventeen participants (mean age 67, SD = 9 years; 12 females) were included. Nine and eight participants were randomized to the exercise and control groups, respectively. Four participants (44%) adhered to exercise training. Compared with any change seen in the control group, those in the exercise group demonstrated greater gains in the peak rate of oxygen consumption (mean difference, 95% confidence interval for between-group difference: 0.19 [0.04–0.33] L min−1) and 6-minute walk distance (52 [12–93] m). No other between-group differences were demonstrated. Conclusions: In people following curative intent treatment for non-small cell lung cancer, 8 weeks of supervised exercise training improved exercise capacity, measured by both laboratory- and field-based exercise tests. These results suggest that this clinical population may benefit from attending exercise training programs.